Kinesiophobia and associated factors among patients with cardiac disease attending cardiac units at hospitals in Addis Ababa, Ethiopia, 2024: a multicentre cross-sectional study - Gashaw Jember Belay; Yohannes Girma Legese; Yihalem Belete; Tewodrose Miheret; Fiseha Sefiwu Zinabu; Foad Akmel (BMJ Open)
Background Kinesiophobia is a catastrophic fear of physical activity due to a patient’s overwhelming concerns and sense of vulnerability about cardiac consequences due to activities. However, there was a lack of information regarding kinesiophobia among patients with cardiac disease, particularly in low- and middle-income countries, including Ethiopia.Aim This study aimed to assess the prevalence of kinesiophobia and its associated factors among patients with cardiac disease attending cardiac units at hospitals in Addis Ababa, Ethiopia.Design An institutional-based multicentre cross-sectional study was conducted.Setting and participants The study was conducted through a systematic random sampling technique in six comprehensive specialised hospitals to select 405 study participants.Primary tool and analysis Kinesiophobia was assessed by the Tampa Scale Kinesiophobia-heart questionnaire. The collected data were analysed on SPSS V.25. Bivariate analysis was used to determine potential candidate variables. Finally, an adjusted OR (AOR) with a p value of <0.05 and a 95% CI was considered statistically significant.Result The prevalence of kinesiophobia was 67.4% (95% CI: 62.6% to 72%). An older age group (AOR=3.84; 95% CI=1.663 to 8.864), cardiac function classification class II (AOR=2.639; 95% CI=1.090 to 6.388), class III (AOR=5.646; 95% CI=2.299 to 13.868), class IV (AOR=9.229; 95% CI=3.026 to 28.142), being physically inactive (AOR=2.642; 95% CI=1.490 to 4.685), being anxious (AOR=2.730; 95% CI=1.487 to 5.011) and moderate (AOR=2.172; 95% CI=1.063 to 4.437) and high perceived threat (AOR=6.146; 95% CI=2.955 to 12.786) were significantly associated with kinesiophobia.Conclusion The results of this research imply that kinesiophobia is a common health concern among patients with cardiac disease. Being above 50 years, advanced stage of cardiac disease, physical inactivity, anxiety and having higher threat illness perceptions were significantly associated with kinesiophobia among patients with cardiac disease.